Desain Laboratorium Virtual Berorientasi Green Chemistry dengan Proyek untuk Meningkatkan Hasil Belajar pada Pengajaran Gravimetri - Anggun Vitanida Simanjuntak; Manihar Situmorang (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
Gravimetry learning in analytical chemistry faces limitations in tools, the risk of using hazardous chemicals, and low student learning outcomes. This study aims to develop and test the effectiveness of a project-based green chemistry-oriented virtual laboratory on gravimetry material. The research method used is Research and Development (R&D) with a 4D model followed by a quasi-experimental trial using a pretest-posttest non-equivalent control group design. The research subjects consisted of 34 students in the experimental class and 38 students in the control class. The results showed that the increase in learning outcomes was higher in the experimental class (N-Gain = 0.63; medium category) compared to the control class (N-Gain = 0.54; medium category). The t-test results showed a significant difference (t count = 2.868 > t table = 2.000; p < 0.05), so that the project-based green chemistry-oriented virtual laboratory was proven to be more effective than conventional learning. These findings indicate that the integration of virtual laboratories, green chemistry, and project-based learning is effective in improving student learning outcomes and has the potential to be a safe and sustainable alternative to practical learning.